Perbandingan Implementasi E-Procurement Di Indonesia Dan Australia - Gulo, Diwi Putri; Dompak, Timbul; Khairina, Etika (Prosiding, 2024)
This research compares the implementation of e-procurement in Indonesia and Australia using a qualitative literature study method. Despite similar processes, there are differences in approach, system features, data security, transparency and accountability. Indonesia uses the SPSE one-stop system, while Australia uses a decentralized approach through AusTender. Both countries face challenges in e- procurement adoption such as change resistance, technological infrastructure, and complex system integration. Support programs and user training are key to effective implementation. Efforts to increase transparency and accountability continue despite concerns about limited information and lack of standardization of reporting. This research highlights best practices, challenges and collaboration potential for further e-procurement development.